THE BUSINESS MODEL: WAY TO HIGHLIGHT THE CAUSE-AND-EFFECT RELATIONSHIPS BETWEEN STAKEHOLDERS AND MONEY - IONELA SAMUIL (Annals of the University of Petrosani: Economics)
The business model is foundational to every organization, evolving through phases from initial definitions and classifications to innovations and the current development of open network-based models with systematic monitoring and strategy mapping capabilities. This evolution continually gives rise to specialized versions. Entrepreneurs widely embrace the CANVAS business model due to its visual nature, facilitating the visualization of business potential. Unlike mere lists, its nine dimensions are structured into a table that visualizes relationships between components. The model divides into left and right sections, with the value proposition central between them, fostering mapping, discussion, design, and innovation across the nine dimensions. In contrast, static business models face criticism for their inflexibility, prompting the rise of dynamic business models in dynamic economic landscapes. Dynamic models integrate traditional frameworks with dynamic system modeling, mapping value creation elements into causal relationships. Simulation enables analysts and entrepreneurs to understand how the organization responds to strategic changes in terms of performance, innovation, and value creation. The analysis of the evolution of business models, the exploration of the applicability of the CANVAS model, the examination of the advantages of dynamic models, and the study of the impact of dynamic systems modeling (SD) reflect the central themes of the research. These objectives are aimed at an in-depth exploration of the concept of business models within the context of contemporary dynamic environments.